MINAT BELAJAR SISWA SEKOLAH DASAR TERHADAP MATERI “GREETINGS AND INTRODUCTION” DALAM PEMBELAJARAN BAHASA INGGRIS - Bintang Adriani; Eva Betty Simajuntak; Elsa Renata; Gisela Agita Sofia; Luthfi Vivia Diwani; Lyra Kartika; Yusma Fadhilah (Jurnal Merah Putih Sekolah Dasar, 2026)
This study aims to describe the level of elementary school students’ interest in learning the material “Greetings and Introduction” in English lessons. This research employed a descriptive quantitative approach using a Likert-scale questionnaire consisting of 10 statements administered to 21 fifth-grade students. The results showed that the average score of students’ learning interest was 39.48, which falls into the high category. These findings indicate that students demonstrate strong enthusiasm for learning English, influenced by interest in the material, ease of understanding, and enjoyable learning methods. This study highlights the importance of implementing engaging and contextual learning strategies to maintain and enhance students’ interest in English learning at the elementary school level.